Pengaruh Penerapan Game Based Learning Terhadap Motivasi Belajar Siswa Sekolah Dasar - Isti Septianing; Lina Melati; Nabila Deo Cantika; Wannuraniza Destiani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Curriculum requirements require educators to be creative in developing learning styles. However, in reality, most educators in Indonesia currently only provide the things that are available in teaching modules and focus on fulfilling curriculum material without considering the expected learning outcomes. To overcome this problem, educators need to modify learning styles by providing learning innovations. One alternative that can be applied to elementary school students is to apply the Game Based Learning learning model. Therefore, the aim of the research is to find out the effect of implementing the Game Based Learning learning model on elementary school students' learning motivation. The literature review was carried out by conducting a literature review which aims to examine the application, factors and impact of Game Based Learning on elementary school students' learning motivation. Literature searches were carried out using the Google Scholar database for the 2013-2023 period. Based on article extraction, 6 articles were found that were appropriate to the discussion, which shows that there are several stages in the game based learning model, namely (1) identifying learning objectives. (2) determine the big idea. (3) create a game scenario. (4) create a learning activity design. (5) create groups. (6) apply game dynamics. In its application, GBL has several factors, namely: game design, instructional support, motivational aspects, and the ability to develop multiple intelligences. The impact of implementing GBL itself, among other things, can increase student learning motivation, increase student literacy motivation, and certainly have an effect on student learning outcomes.